Anthony Kenny narratore della filosofia medievale (Doctor Virtualis, 2021)
In an era, like the present one, devoted to specialism, few authors are willing to write a history of philosophy that aspires to cover an entire period, such as the medieval one and, even less, those who attempt to draw up a global history of philosophy. The sectoriality has many advantages, but at least one defect, that is to avoid a unitary narrative which, although necessarily partial and not complete, is capable of offering an overview by staging the main philosophers, aggregated into currents, and the fundamental directions of speculative thought. The risk of formulating a unitary narrative of philosophy, as the sole author, was faced by Anthony Kenny, publishing four volumes of a New History of Western Philosophy. The second of these volumes is dedicated to medieval philosophy and the present contribution intends to contextualize its genesis, paying special attention to the two sources Kenny refers to (Russell's and Copleston's histories of philosophy) to then clarify the criteria used by Kenny in what he himself defines as a narration and to critically examine the results achieved.